Molecular epidemiology of clinical and carrier strains of methicillin resistant Staphylococcus aureus (MRSA) in the hospital settings of north India - Dar Mohammad J; Bhat Khalid H; Rizwan Mohammed; Khan Mohammed A; Ali Asif; Khan Jamal A; Thoker Manzoor A; Dar Javid A; Ahmed Niyaz; Ahmad Shamim (BMC, 2006)
Abstract Background The study was conducted between 2000 and 2003 on 750 human subjects, yielding 850 strains of staphylococci from clinical specimens (575), nasal cultures of hospitalized patients (100) and eye & nasal sources of hospital workers (50 & 125 respectively) in order to determine their epidemiology, acquisition and dissemination of resistance genes. Methods Organisms from clinical samples were isolated, cultured and identified as per the standard routine procedures. Susceptibility was measured by the agar diffusion method, as recommended by the Nat ional Committee for Clinical Laboratory Standards (NCCLS). The modified method of Birnboin and Takahashi was used for isolation of plasmids from staphylococci. Pulsed-field gel electrophoresis (PFGE) typing of clinical and carrier Methicillin resistant Staphylococcus aureus (MRSA) strains isolated during our study was performed as described previously. Results It was shown that 35.1% of Staphylococcus aureus and 22.5% of coagulase-negative staphylococcal isolates were resistant to methicillin. Highest percentage of MRSA (35.5%) was found in pus specimens (n = 151). The multiple drug resistance of all MRSA (n = 180) and Methicillin resistant Coagulase-negative Staphylococcus aureus (MRCNS) (n = 76) isolates was detected. In case of both methicillin-resistant as well as methicillin-sensitive Saphylococcal isolates zero resistance was found to vancomycin where as highest resistance was found to penicillin G followed by ampicillin. It was shown that the major reservoir of methicillin resistant staphylococci in hospitals are colonized/infected inpatients and colonized hospital workers, with carriers at risk for developing endogenous infection or transmitting infection to health care workers and patients. The results were confirmed by molecular typing using PFGE by SmaI-digestion. It was shown that the resistant markers G and T got transferred from clinical S. aureus (JS-105) to carrier S. aureus (JN-49) and the ciprofloxacin (Cf) and erythromycin (E) resistance seemed to be chromosomal mediated. In one of the experiments, plasmid pJMR1O from Staphylococcus aureus coding for ampicillin (A), gentamicin (G) and amikacin (Ak) resistance was transformed into Escherichia coli. The minimal inhibitory concentrations (MICs) for A and G were lower in E. coli than in S. aureus. However, the MIC for Ak was higher in E. coli transformants than in S. aureus. Conclusion There is a progressive increase in MRSA prevalence and multi-drug resistance in staphylococci. Vancomycin is still the drug of choice for MRSA infections. The major reservoir of methicillin resistant staphylococci in hospitals is colonized/infected inpatients and colonized hospital workers. Resistance transfer from staphylococci to E. coli as well as from clinical to carrier staphylococci due to antibiotic stress seemed to be an alarming threat to antimicrobial chemotherapy.